Robbins and Cotran review of pathology - Klatt Edward C. (Saunders/Elsevier, 2010)
This easy-to-use new edition of 'Robbins and Cotran Review of Pathology' helps you effectively master the most important principles and facts in pathology. More than 1100 questions - many new to this edition - reinforce the fundamentals of gross and microscopic pathology as well as the latest findings in molecular biology and genetics.